2012
DOI: 10.1021/bi301005z
|View full text |Cite
|
Sign up to set email alerts
|

Local Unfolding Is Required for the Site-Specific Protein Modification by Transglutaminase

Abstract: The transglutaminase (TGase) from Streptomyces mobaraensis catalyzes transamidation reactions in a protein substrate leading to the modification of the side chains of Gln and Lys residues according to the A-CONH(2) + H(2)N-B → A-CONH-B + NH(3) reaction, where both A and B can be a protein or a ligand. A noteworthy property of TGase is its susbstrate specificity, so that often only a few specific Gln or Lys residues can be modified in a globular protein. The molecular features of a globular protein dictating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 63 publications
4
77
1
1
Order By: Relevance
“…Therefore while in the molecules of Sugimura et al [16] the arginine was found to be more available for productive interactions with the enzyme, in our study broad chain flexibility renders this residue less prone to interaction or even able to disrupt the interaction. This hypothesis fits well with the concept that the catalytic reaction strongly depends on both the chemical and structural environment of the glutamine residue [8,13].…”
Section: Lqsp Is a New Efficient Transglutaminase Substratesupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore while in the molecules of Sugimura et al [16] the arginine was found to be more available for productive interactions with the enzyme, in our study broad chain flexibility renders this residue less prone to interaction or even able to disrupt the interaction. This hypothesis fits well with the concept that the catalytic reaction strongly depends on both the chemical and structural environment of the glutamine residue [8,13].…”
Section: Lqsp Is a New Efficient Transglutaminase Substratesupporting
confidence: 88%
“…The substrate specificity of TGases has been investigated by using both synthetic peptides [10][11][12] and model proteins [13]. The literature show we still have much to learn about TGases [14].…”
Section: Biotech Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of lysine residues with glutamine substrates was difficult because of premature, irreversible, enzymatic hydrolysis of the corresponding glutamine substrates to glutamate. Recently, Spolaore et al [29] showed in an elegant study that site-specific protein modification by transglutaminase requires the glutamine and lysine residues to be either in a flexible or a locally unfolded region of the protein. This could also explain why the site-specific derivatization of antibody chCE7agl by mTGase with a Gln substrate could not be accomplished as there is not a lysine residue embedded in such a flexible or unfolded structure.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the cross-links were introduced by MTG only after the collagen had been at least partially heat-denatured, supporting the correlation between structural disorder of the target and recognition by MTG. To further investigate the importance of secondary structure and MTG’s apparent preference for flexible polypeptide regions, the reactivity of MTG towards apoMb, α-lactalbumin (α-LA) and fragment 205-316 of thermolysin was analyzed [53]. These extensively studied proteins are models of α-helices, β-sheets and unstructured regions, respectively.…”
Section: Substrate Specificitymentioning
confidence: 99%